An analysis of protective and risk factors associated with no formal contact with the criminal justice system in a nationally representative sample of males and females - Rima, Dzhansarayeva (Journal of crime and justice, 2023)
Criminological research is largely focused on understanding the causes, correlates, and pathways to criminal behavior and contact with the criminal justice system. An equally important issue that has received comparatively less attention is a focus on understanding the correlates and causes of abstinence from criminal behavior and contact with the criminal justice system. The current study was designed to analyze the potential protective and risk factors associated with having no contact with the criminal justice system – that is, abstaining from criminal justice system contact. To do so, the authors analyzed data drawn from the National Longitudinal Study of Adolescent to Adult Health (Add Health). The results revealed that about 72 percent of respondents abstained from contact with the criminal justice system. Moreover, religion and intelligence were associated with increases in the odds of abstinence while low self-control, delinquent peers, and victimization were associated with reductions in the odds of abstinence for both males and females. We conclude by discussing the limitations of the study and directions for future research.